Harnessing affinity-based protein profiling to reveal a novel target of nintedanib. Issue 25 (26th February 2021) - Chen, Xiong; Li, Menglin; Li, Manru; Wang, Dongmei; Zhang, Jinlan
Abstract : We identified tripeptidyl-peptidase 1 (TPP1) as one of the direct targets of nintedanib (NDNB) employing clickable photoaffinity probes, which provides insights into the functional meaning of the well-known IPF therapeutic drug. Abstract : Nintedanib (BIBF1120), a triple angiokinase inhibitor, was first approved for idiopathic pulmonary fibrosis (IPF) therapy and is also efficacious for lung carcinoma, and interstitial lung diseases, far beyond its inhibition of VEGFR/PDGFR/FGFR. We identified tripeptidyl-peptidase 1 (TPP1) as one of the direct targets of nintedanib employing the affinity-based protein profiling (A f BPP) technique. This may be a new mechanism for nintedanib's role different from tyrosine kinase inhibition.